Empirical Reasons, Theoretical Explanation, and Theoretical Framework on Why People Engage in Instant Justice - Asafo-Adjei, Edward (2021)
The phenomenon of Instant Justice undermines human rights, the rule of law, and it is a concern for the development of democracy. Instant Justice is prevalent in many states especially in Africa, thereby generating research, intellectual discourse and public debate on the phenomenon. Instant Justice is of great concern therefore this paper aims to contribute to the intellectual discourse by providing understanding and explanation on the reasons why people engage in Instant Justice. The paper employs exploratory research methodology grounded in the use of desk research technique and a combination of trend and content analytical procedure. The paper is focused on achieving three objectives, the first, which is to review existing literature on some of the relevant empirical studies that have been conducted to determine the reasons why people engage in Instant Justice. It is further the objective of this paper, based on the empirical review and reasons established, to review relevant theories to provide theoretical explanation on why people engage in Instant Justice. Finally, it is the objective of this paper to develop a Theoretical Framework on Instant Justice using identified constructs from the empirical review and the theories reviewed. Significantly, the review of empirical literature, review of theories and Theoretical Framework developed provides reliable information that will equip state governments and other stakeholders to institute measures and structures to address the prevalence of Instant Justice. Again, the Theoretical Framework provides researchers with various identified constructs and how they correlate to enhance and guide further studies on Instant Justice. Keywords: Instant Justice, Mob Justice, Vigilante Justice, Criminal Justice DOI: 10.7176/PPAR/11-4-02 Publication date:May 31st 202